The effect of trans-provincial immediate reimbursement for healthcare expenses on inequity in the utilization of healthcare services for migrants - Mei Zhou; Longwei Zhang; Yunjia Liang; Yuxiao Chen (BMC, 2024)
Abstract Background Improving the accessibility of public services for migrants is an important endeavor to promote equity in economic and social development. As a response to the large-scale movement of migrants and the fragmentation of China's health insurance system, the Chinese Government has launched a policy of trans-provincial immediate reimbursement for healthcare expenses. The present study hopes to examine the effect of immediate reimbursement policy on the utilization of healthcare services for migrants in China. Methods This study used two waves of data from the China Migrants Dynamic Survey (CMDS) collected in 2013 and 2017, with the sample comprising 13,540 individuals. We constructed a difference-in-differences (DID) model to investigate the impact of the policy on the utilization of healthcare services for migrants. Meanwhile, we also analyzed the heterogeneity of the policy effect by grouping the samples by industry, gender, income, and education level. Results The results found that the trans-provincial immediate reimbursement significantly promoted the probability of migrants' utilization of quality healthcare services (average treatment effect on the treated = 0.072, p < 0.05). Heterogeneity analyses revealed that the policy effect was more pronounced among higher-income and better-educated migrants. In addition, the policy effect was more significant for female migrants, and the benefits were more marked for migrants in high-risk industries. Conclusions The trans-provincial immediate reimbursement policy has improved the inequity of healthcare services utilization among migrants as a whole; however, within the migrants, inequity still exists. More attention should also be paid to low-income or low-education groups in future policy design.